Análisis control interno del área de caja de la Empresa Moda Latina - Peñafiel Cajape, Melida Suamy (2024)
The present research work to obtain a university degree, presents the design of a proposal for analysis of the internal control of the cash area of the Moda Latina company, which aims to guarantee the veracity and reliability of the operations carried out in this area. of the Moda Latina company, by identifying an evaluation of each of the components of internal control. For the development, it is essential to design the approach of the proposal where the problem statement and definition of the line of research are found, followed by an enrichment of knowledge about the internal control of the company's cash area by consulting works in different sources. national and international, information that will allow the design of strategies that allow adequate internal control of the cash that is managed within the Moda Latina company, in the same way it is necessary to define the legal framework to which the company must be attached. As a next point, it is important to specify that the work has a mixed approach, since on the one hand it is necessary to carry out a qualitative analysis, since it is about understanding the different processes carried out in the cashier area, as well as being based on operations. numerical for the tabulation of the information collected through the applied tools, and subsequently, according to the results collected about the internal control of the cash area, proceed to develop a proposal that is in accordance with the needs of the company.